Implementation of the Borda Method for Selecting Winners in the Tahfeez Tahmeed and Prayer Competition by DPD Recital Alhidayah - Marpaung, Miftah Rizki; Kurniawan, Edi; Rahayu, Elly (invotek, 2024)
Tahfeez, tahmeed, and prayer competitions that are routinely held by DPD Recital Alhidayah often experience obstacles in the assessment process due to the lack of a structured and computerized system, thereby reducing the efficiency and accuracy of assessment. This problem has become increasingly complex with a large number of participants and the absence of standard procedures in awarding scores. This research was conducted to develop a decision support system that can assist the judges in determining the winner of the competition objectively, efficiently, and transparently. The method used is the Borda Method, which is a rank-based decision-making method that is effective in accommodating the assessment of many judges and criteria. The system was built using the PHP programming language and MySQL database, and was designed with a quantitative approach through the processing of participant scores based on three main criteria: tajweed, fluency, and rhythm. The implementation of this system allows judges to conduct assessments digitally, where the grades given are automatically processed and ranked using the Borda Method. The results of the study show that this system can speed up the assessment process and announcement of the winner from the previous 4–5 days to instant after the input of the score is completed. This system also increases transparency, reduces subjectivity, and ensures consistency in scoring. Thus, this system becomes a relevant and applicable solution to support professionalism in religious competitions.